2013
DOI: 10.15407/ujpe58.08.0742
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysical Characteristics of Near-Surface Layers in p-Si Crystals with Sputtered Al Films and Subjected to Elastic Deformation

Abstract: PACS 61.50. Ks, 61.72.Ff, 68.35.bg The deposition of Al film onto the (111) surface of a p-Si crystal was shown to induce a deformation in the near-surface layer of the latter. Provided that the crystal strain is elastic and uniaxial, the gettering of defects in the near-surface layer is observed, which is confirmed by a change in the dependence of the specimen resistance on the elastic strain magnitude. The maximum depth of the defect capture has been calculated on the basis of the energy of interaction b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 2 publications
0
9
0
4
Order By: Relevance
“… Radiation-stimulated decrease in the reverse current, which is proportional to the density of the dislocations, is stipulated by generation of the minority carriers and their partial localization at the vacancies and dislocations. That is why one can say that the defect state of the nearsurface layer of the silicon crystals where the SBSs are formed represents a crucial factor in the process of radiation-stimulated changes of their electro-physical characteristics (Pavlyk et al, 2013). The processes associated with the effect of X-rays are less important.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Radiation-stimulated decrease in the reverse current, which is proportional to the density of the dislocations, is stipulated by generation of the minority carriers and their partial localization at the vacancies and dislocations. That is why one can say that the defect state of the nearsurface layer of the silicon crystals where the SBSs are formed represents a crucial factor in the process of radiation-stimulated changes of their electro-physical characteristics (Pavlyk et al, 2013). The processes associated with the effect of X-rays are less important.…”
Section: Resultsmentioning
confidence: 99%
“…The modeling of the underlying physical processes carried out by Pavlyk et al (2013) has shown that the near-contact layers of Al and Si in the SBS are strained. Having performed similar calculations for the bismuth films, we arrive at considerably smaller mechanical tensions in the contact areas of the bismuth-silicon structures.…”
Section: Resultsmentioning
confidence: 99%
“…As Lukjanitsa`shows in paper [ 17 ], this energy level maybe responds to the vacancy defects. Since the process of plastic deformation increases the intensity of diffusion of impurities and defects from the surface into the volume of silicon, it is also possible to reverse processes: diffusion of defects by dislocations to the surface and localization in the surface layer [ 7 ]. As the concentration of linear defects on the crystal surface increased by five orders of magnitude, then occurrence probability of dislocation and point defect complexes may also increase.…”
Section: Resultsmentioning
confidence: 99%
“…As the Cz–Si crystals contain high concentration of oxygen, the plastic deformation provokes so called defects clustering process (mainly oxygen precipitates) [ 6 ]. During the annealing in oxygen atmosphere T = 1300 K, O I precipitates, which were formed after plastic deformation, acting as an additional channel of dislocations formation [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation